Editorial - Mackinlay, Elizabeth; Nakata, Martin; Barney, Katelyn (The Australian Journal of Indigenous Education, 2017)
We are very pleased to bring you Volume 46.2 of the Australian Journal of Indigenous Education. In conversation as Indigenous and non-Indigenous educators working towards social justice in education, the papers in this Volume explore key questions across school, tertiary education and policy contexts. One of the key challenges for those of us working in Indigenous education landscapes in Australia and globally continues to be the ways in which policy plays out and is performed through high stakes testing of various shapes and forms. Like policy itself, ‘testing’ is linked to discourse about Indigenous peoples, capacity for educational ‘success’ and the kinds of pedagogies and teacher-ly performativities that might be enacted to achieve such outcomes. This is a necessarily complex landscape and the discussions we present in this Volume ask us to take pause and consider the relationship between policy, testing and educational practice and the ways these interface with Indigenous ways of being, doing and knowing.